Stroke and Bleeding Risk Assessments in Patients With Atrial Fibrillation: Concepts and Controversies - Ding, Wern Yew; Harrison, Stephanie; Gupta, Dhiraj; Lip, Gregory Y. H.; Lane, Deirdre A. (Frontiers in Medicine, 2020)
Risk assessments are an important element in the management of patients with atrial fibrillation (AF). In this review, we aim to discuss the concepts and controversies surrounding the various risk factors for stroke and bleeding in AF. Indeed, there are a variety of clinical, electrical, biological and genetic markers to guide stroke and bleeding risk assessments in AF. The more common factors have been used to formulate risk stratification scores. Some risk factors have shown promise, but others remain less well-defined. Our aim is to discuss concepts and controversies surrounding current evidence of risk factors for stroke and bleeding assessments in AF.